Do Constancy Mechanisms Save Distal Content?. (25th January 2019) - Garson, Justin
Abstract: In this journal, Schulte develops a novel solution to the problem of distal content: by virtue of what is a mental representation about a distal object (say, a snake) rather than a more proximal cause of that representation (say, a snake-shaped retinal impression)? Schulte maintains that in order for a (sensory-perceptual) representation to have a distal content, it must be produced by a constancy mechanism, along with two other conditions. I raise three objections to his solution. First, a core component of Schulte's solution is just a restrictive version of Dretske's solution, but Schulte gives no argument for his restriction. Second, his proposed solution to a disjunction problem (his 'naturalness' condition) is ad hoc. Finally, his 'far-out' version of the distality problem is not a version of the distality problem at all. I conclude that Dretske's solution is preferable to Schulte's.